2014
DOI: 10.1097/ijg.0b013e31825afc9d
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Fluctuation in Patients With Primary Open-angle Glaucoma Combined With High Myopia

Abstract: High-tension POAG patients with high myopia on only pharmacological glaucoma therapy have significantly greater IOP fluctuations after moderate and heavy exercise and do not have greater 24-hour IOP fluctuations at resting conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 18 publications
1
18
0
2
Order By: Relevance
“…An additional and significant IOP reduction of 2.78 mmHg after 10 min of exercise on a cycle ergometer at an intensity of 20% maximum watt ( W max ), and 4.90 mmHg after 5 min of exercise at 60% W max , was also observed in patients with glaucoma on topical PGA instillation alone (Yang et al. ). Therefore, dynamic exercise induced an IOP reduction in patients with glaucoma, which was independent of the use of antiglaucoma agents.…”
Section: Physical Exercise and Iop Controlmentioning
confidence: 92%
See 3 more Smart Citations
“…An additional and significant IOP reduction of 2.78 mmHg after 10 min of exercise on a cycle ergometer at an intensity of 20% maximum watt ( W max ), and 4.90 mmHg after 5 min of exercise at 60% W max , was also observed in patients with glaucoma on topical PGA instillation alone (Yang et al. ). Therefore, dynamic exercise induced an IOP reduction in patients with glaucoma, which was independent of the use of antiglaucoma agents.…”
Section: Physical Exercise and Iop Controlmentioning
confidence: 92%
“…Yang et al. () also suggested a more significant IOP reduction effect with more intensive exercise. Conte's group found that both high‐intensity‐interval training (HIT) and continuous moderate exercise (CME) were effective in IOP reduction in young healthy subjects.…”
Section: Physical Exercise and Iop Controlmentioning
confidence: 94%
See 2 more Smart Citations
“…However, since IOP fluctuates over the course of a 24-h time period (Barkana et al, 2006;Konstas et al, 1997;Loewen et al, 2010;Song et al, 2014;Yang et al, 2014), continuous IOP monitoring would offer a more complete picture of true IOP. Nocturnal IOP measurements are of interest because IOP is higher in the habitual, supine position in many patients during nighttime hours (Liu and Weinreb, 2014).…”
Section: Iop: New Trendsmentioning
confidence: 99%